Embedding Epistemic Modals - Dorr, C; Hawthorne, J (Oxford University Press, 2013)
Seth Yalcin has pointed out some puzzling facts about the behaviour of epistemic modals in certain embedded contexts. For example, conditionals that begin 'If it is raining and it might not be raining,...' sound unacceptable, unlike conditionals that begin 'If it is raining and I don't know it,...'. These facts pose a prima facie problem for an orthodox treatment of epistemic modals as expressing propositions about the knowledge of some contextually specified individual or group. This paper develops an explanation of the puzzling facts about embedding within an orthodox framework. © 2013 Dorr and Hawthorne.